Founding Family Ownership and Myopic R&D Investment Behavior. (July 2019) - Tsao, Shou-Min; Chang, Yin-Wei; Koh, Kevin
This study examines whether founding family ownership mitigates or exacerbates myopic R&D investment behavior. The prior literature suggests that managers are more likely to engage in earnings management—such as myopic R&D reduction—when firms are facing problematic situations, such as (a) a small earnings decline or loss and/or (b) a debt covenant violation. Employing a sample of R&D-intensive firms in Taiwan, we find that founding family ownership mitigates myopic R&D investment behavior in both problematic situations. These findings are consistent with the "Family Identity" dimension of socioemotional wealth (SEW) theory in which family firms have substantial incentives to protect the family's reputation and to avoid actions that reduce long-run firm value. In supplementary analyses, we find that family firms continue to avoid myopic R&D reduction under these two situations even when they have limited opportunities to engage in accrual-based earnings management. Furthermore, family CEOs are shown to be responsible for mitigating the tendencies of firms to engage in myopic R&D investment behavior, and the mitigating impact on myopic R&D investment behavior is found only in family firms without control-enhancing mechanisms such as voting–cash flow rights divergence. Our findings are not driven by blockholder effects because our results remain robust after controlling for the presence of institutional investors and nonfamily insiders.